2017
DOI: 10.3389/fmicb.2017.00887
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Androgenic-Mutagenic Compounds and Potential Autochthonous Bacterial Communities during In Situ Bioremediation of Post-methanated Distillery Sludge

Abstract: Sugarcane-molasses-based post-methanated distillery waste is well known for its toxicity, causing adverse effects on aquatic flora and fauna. Here, it has been demonstrated that there is an abundant mixture of androgenic and mutagenic compounds both in distillery sludge and leachate. Gas chromatography-mass spectrometry (GC-MS) analysis showed dodecanoic acid, octadecanoic acid, n-pentadecanoic acid, hexadecanoic acid, β-sitosterol, stigmasterol, β-sitosterol trimethyl ether, heptacosane, dotriacontane, lanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The common residual complex organic pollutants detected were dibenzoparadoxin and dibenzofurans, 4-isopropoxybutyric acid, 3,7,11,15,18-pentaoxa-2,19-disid aneicosane, butane-1-ol, hexahydropyrrole (1,2A) pyrazine-1,4-dione, 6-chlorohexanoic acid, 2,5-3-6-bis(phenylmethyl)piperazinedione, 1-chlorooctadane, 1,2-benzene carboxylic acid, 3-tetradecyl ester benzene acetic acid, 2- hydroxymethylcyclopropane carboxylic acid, 2-methoxyphenol phthalic anhydride, 2,6-dimethoxyphenol, 2-methoxy-4-ethylphenol, 3-allyl-6-methoxyphenol, and 2-methoxy-4(1-propenyl) (Chandra and Singh, 2012). This study also indicated that these compounds exhibited an endocrine-disrupting effect on aquatic organisms due to the presence of endocrine-disrupting chemicals (EDCs) (Orrego et al, 2009; Chandra and Kumar, 2017); however, detailed knowledge regarding the estrogenic and androgenic potential of these compounds toward aquatic organisms is lacking. The presence of organic pollutants in the final effluent discharge indicated that the microbial community present in the wastewater was unable to degrade them due to lack of adequate nutrients; hence, optimization of bacterial growth conditions by addition of nutrient or environmental conditions may be an effective approach for detoxification of such effluents.…”
Section: Introductionmentioning
confidence: 94%
“…The common residual complex organic pollutants detected were dibenzoparadoxin and dibenzofurans, 4-isopropoxybutyric acid, 3,7,11,15,18-pentaoxa-2,19-disid aneicosane, butane-1-ol, hexahydropyrrole (1,2A) pyrazine-1,4-dione, 6-chlorohexanoic acid, 2,5-3-6-bis(phenylmethyl)piperazinedione, 1-chlorooctadane, 1,2-benzene carboxylic acid, 3-tetradecyl ester benzene acetic acid, 2- hydroxymethylcyclopropane carboxylic acid, 2-methoxyphenol phthalic anhydride, 2,6-dimethoxyphenol, 2-methoxy-4-ethylphenol, 3-allyl-6-methoxyphenol, and 2-methoxy-4(1-propenyl) (Chandra and Singh, 2012). This study also indicated that these compounds exhibited an endocrine-disrupting effect on aquatic organisms due to the presence of endocrine-disrupting chemicals (EDCs) (Orrego et al, 2009; Chandra and Kumar, 2017); however, detailed knowledge regarding the estrogenic and androgenic potential of these compounds toward aquatic organisms is lacking. The presence of organic pollutants in the final effluent discharge indicated that the microbial community present in the wastewater was unable to degrade them due to lack of adequate nutrients; hence, optimization of bacterial growth conditions by addition of nutrient or environmental conditions may be an effective approach for detoxification of such effluents.…”
Section: Introductionmentioning
confidence: 94%
“…The BOD/COD ratio of untreated melanoidins sample was found 0.39. The high pH of control sample might be due to the binding of high concentrations of soluble salts and heavy metals with melanoidins (Chandra and Kumar 2017b;).…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…Therefore, high TDS of solution is found in this study. In addition, the high content of heavy metals in distillery effluent could be due to the corrosive effect of sugarcane juice during the sugar manufacturing process Chandra and Kumar 2017b).…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…Examining the bacterial composition of hydrocarbon-contaminated tropical African soil, Salam and collegues found uncultured genera that were involved in the natural attenuation of hydrocarbons (Salam et al 2017). Furthermore, Chandra and Kumar detected uncultured bacterial members of the microbial community in a post-methanated distillery sludge (PMDS), which potentially played a significant role in neutralizing recalcitrant pollutants in distillery wastes and decreasing phyto-and genotoxicity (Chandra and Kumar 2017). In addition to molecular approaches, the targeted isolation and resuscitation of previously uncultured bacteria by growth promoting factors have been gaining more attention in the past decade.…”
Section: Exploring the Environmental Potential Of Uncultivated Bacteriamentioning
confidence: 99%